LITERASI LARANGAN POLITISASI SARA DALAM PEMILU BAGI WARGA RAMBAH HILIR PEKANBARU - Andrizal, Andrizal; Simamora, Birman; Nazario, Rafael (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This article focuses on the issue of the importance of partnerships for residents or communities in the city of Pekanbaru who gather in the community organization “Perhimpunan Keluarga Rambah Hilir” (PKRH) regarding the issue of the 2024 Election. The phenomenon in the field shows that there are still many PKRH residents who lack knowledge and ignore the prohibition on politicization of Ethnicity, Religion and Race (SARA) in the 2024 election. The target of this service activity is to increase knowledge and understanding of the target audience regarding partner problems. The solution offered and agreed upon by the proposing team and partners in overcoming the priority problems faced by partners is that it is necessary to conduct outreach or deliver material in the form of counseling and discussions. The method of this activity uses the lecture methodwhile the lecturer delivers the material, on that occasion, participants are free to ask questions and answers with the lecturer simultaneously. The details of this method are Material Delivery and Interactive dialogue. The dialogue mode has carried out as participants brainstorming activity to obtain opinion of such problems, aspirations, suggestions, ideas and solutions. The Partner expresses willingness, provides time and place, and mobilizes the community as the target audience. The output that will be produced according to this community service activity plan is: for partners, of course, increasing the understanding about the prohibitions and negative impacts of the politicization of SARA in elections.